A Transcriptomic Analysis of Stylo [Stylosanthes guianensis (Aubl.) Sw.] Provides Novel Insights Into the Basis of Salinity Tolerance - Liu, Yiming; Kong, Danyu; Yang, Hubiao; Douxchamps, Sabine; Atieno, Mary; Xu, Bin; Wang, Wenqiang; Liu, Guodao (Frontiers in Sustainable Food Systems, 2022)
Tropical areas have a large distribution of saline soils and tidal flats with a high salinity level. Salinity stress is a key factor limiting the widespread use of tropical forage such as Stylosanthes guianensis (Aubl.) Sw. This study was designed to screen the salinity tolerance of 84 S. guianensis accessions; In a greenhouse experiment, plants were subjected to Hoagland solution or Hoagland solution with 200 mM NaCl for up to 15 days. Salinity tolerant accession CIAT11365 and salinity sensitive accession FM05-2 were obtained based on withered leaf rate (WLR). Further verification of salinity tolerance in CIAT11365 and FM05-2 with different salinity gradients showed that salinity stress increased WLR and decreased relative chlorophyll content (SPAD), maximum photochemical efficiency of photosystem II (Fv/Fm), and photosynthetic rate (Pn) in FM05-2, but CIAT11365 exhibited lower WLR and higher SPAD, Fv/Fm, and Pn. Leaf RNA-Seq revealed that Ca2+ signal transduction and Na+ transport ability, salinity tolerance-related transcription factors and antioxidant ability, an increase of auxin, and inhibition of cytokinin may play key roles in CIAT11365 response to salinity stress. The results of this study may contribute to our understanding of the molecular mechanism underlying the responses of S. guianensis to salinity stress and also provide important clues for further study and in-depth characterization of salinity resistance breeding candidate genes in S. guianensis.